AFO 2021
DOI: 10.20938/afo38193200
|View full text |Cite
|
Sign up to set email alerts
|

Predation and prey-caching of Eastern Water Skinks Eulamprus quoyii by nesting Nankeen Kestrels Falco cenchroides in eastern New South Wales

Abstract: The breeding diet of a pair of Nankeen Kestrels Falco cenchroides nesting in Beresfield, eastern New South Wales, in 2020 was investigated. By individual prey species, the diet comprised 61.3% reptiles (including two prey species not previously recorded in the Nankeen Kestrel diet—Eastern Water Skink Eulamprus quoyii and most likely Southern Rainbow Skink Carlia tetradactyla), 9.7% birds (including a new prey species—Superb Fairy-wren Malurus cyaneus), 6.4% invertebrates (two crickets: Grylloidea), 3.2% mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Bollen (1991) found that during the nestling period only the male hunted for the first 2 weeks and he made 0.7 delivery/h to the nest between 0900 and 1900 h and the main prey (by number) was Grass Skink (Paleflecked Garden Sunskink). A recent study by Pryor (2021) reported an average delivery rate over the entire nestling period, to a single young, of 1 prey item/h. The combined rate of delivery of prey by the male and female in 2018 (11.1 items/h) and 2020 (6.0-13.8 items/h over four foraging sessions) was high compared with rates reported when vertebrates were the main prey.…”
Section: Feeding Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Bollen (1991) found that during the nestling period only the male hunted for the first 2 weeks and he made 0.7 delivery/h to the nest between 0900 and 1900 h and the main prey (by number) was Grass Skink (Paleflecked Garden Sunskink). A recent study by Pryor (2021) reported an average delivery rate over the entire nestling period, to a single young, of 1 prey item/h. The combined rate of delivery of prey by the male and female in 2018 (11.1 items/h) and 2020 (6.0-13.8 items/h over four foraging sessions) was high compared with rates reported when vertebrates were the main prey.…”
Section: Feeding Ratesmentioning
confidence: 99%
“…During the feeding of the brood in 2018, the male passed prey to the female on a perch near the nest, a common behaviour of the species (Debus 2019;Pryor 2021).…”
Section: Feeding Ratesmentioning
confidence: 99%
See 2 more Smart Citations